Population pressure and the microeconomy of land management in hills and mountains of developing countries - Templeton, Scott R.; Scherr, Sara J. (International Food Policy Research Institute, 1997)
Concerns about harmful environmental impacts are frequently raised in research and policy debates about population growth in the hills and mountains of developing countries. Although establishing wildlife corridors and biosphere reserves is important for preserving selected biodiverse habitats, for the vast majority of hilly-mountainous lands, the major ecological concerns are for the sustainability of local production systems and for watershed integrity. What matters for sustained use of those lands not only is the number of producers but also what, where and how they produce. Evidence from empirical research indicates that population growth in hills and mountains can lead to land enhancement, degradation, or aspects of both. This can be explained by extending induced innovation theory to address environmental impacts of intensification. Increases in the labor-land endowment ratios of households and in local land demand and labor supply make the opportunity cost of land relative to labor increase. As a result, people use hilly-mountainous land resources more intensively for production and consumption, thus tending to deplete resources and significantly alter habitats. But, at the same time, capital- and labor-intensive methods of replenishing or improving soil productivity may become economically more attractive, production systems that enhance the land if the expected discounted returns are greater than those of systems that degrade the land. Users will choose production systems that enhance the land if the expected discounted returns are greater than those of systems that degrade the land. In addition to population change, other factors—market conditions, local institutions and organizations, information and technology about resource management, and local ecological conditions—determine the returns from various production systems.